Desenvolvimento e caracterização microestrutural de nanocompósitos de matriz de alumínio reforçadas com pentóxido de nióbio nanoestruturado processados por deformação plástica severa utilizando torção sob alta pressão - HPT - Clênio Silva (2020)
Several solvothermal routes for the production of niobium oxide nanoparticles have been studied in partnership with the Department of Chemistry at UFMG. Niobium oxide nanoparticles with nanorods and nanowires morphology were successfully produced. The characterization of these nanoparticles by SEM, X-ray diffraction and TEM revealed to be niobium pentoxide - Nb2O5. Compounds were selected by mixing commercial pure aluminum powder (matrix) with Nb2O5 powders (reinforcement phase) in concentrations of 0.5, 1, 2, 3, 5 and 10%. The selected mixtures were processed by HPT (High Pressure Torsion) with 5 and 10 turns at room temperature. The use of nanostructured Nb2O5 promoted greater matrix interaction and provided excellent results in composites. Significant increase in hardness were observed in relation to the same samples without reinforcements. The shear stresses caused by the induced plastic deformation promoted, at room temperature, the partial reduction of nanowires Nb2O5 by aluminum with the formation of nanometric layers of aluminum oxide (Al2O3) around the reinforcements changing the interface from Nb2O5-Al to Nb2O5-Al2O3-Al. This new hierarchical structure changed the interactions between matrix and reinforcements and promoted a greater transfer of load from the matrix to reinforcements. Complete reduction of Nb2O5 induced by mechanical deformation was observed in nanorods samples with formation of Nb nanoprecipitates, supersaturated solid solution (Nb-Al) and intense Nb segregation towards the grain boundaries and dislocations. Annealing heat treatment at 100oC for 1h carried out on samples with reinforcements, contrary to the conventional, promoted an exceptional increase in hardness, a phenomenon known as "Annealing Induced Hardening" due to the relaxation of the tensions in the grain boundaries, rearrangement in the random configuration of the dislocations for a cluster configuration in addition to an intense segregation of the niobium atoms towards grain boundaries and dislocations.